Evaluating national cause-of-death statistics: principles and application to the case of China - Chalapati Rao; Alan D. Lopez; Gonghuan Yang; Stephen Begg; Jiemin Ma (The World Health Organization, 2005)
Mortality statistics systems provide basic information on the levels and causes of mortality in populations. Only a third of the world's countries have complete civil registration systems that yield adequate cause-specific mortality data for health policy-making and monitoring. This paper describes the development of a set of criteria for evaluating the quality of national mortality statistics and applies them to China as an example. The criteria cover a range of structural, statistical and technical aspects of national mortality data. Little is known about cause-of-death data in China, which is home to roughly one-fifth of the world's population. These criteria were used to evaluate the utility of data from two mortality statistics systems in use in China, namely the Ministry of Health-Vital Registration (MOH-VR) system and the Disease Surveillance Point (DSP) system. We concluded that mortality registration was incomplete in both. No statistics were available for geographical subdivisions of the country to inform resource allocation or for the monitoring of health programmes. Compilation and publication of statistics is irregular in the case of the DSP, and they are not made publicly available at all by the MOH-VR. More research is required to measure the content validity of cause-of-death attribution in the two systems, especially due to the use of verbal autopsy methods in rural areas. This framework of criteria-based evaluation is recommended for the evaluation of national mortality data in developing countries to determine their utility and to guide efforts to improve their value for guiding policy.